Performance of diesel engine using hydrogen as a fuel - Nur Izzati , Khairuddin (2012)
Among the alternative fuels, hydrogen shows great potential in the near future. In the present study, hydrogen utilization as diesel engine fuel was investigated. Hydrogen cannot be used directly in a diesel engine due to its autoignition temperature higher than that of diesel fuel. One alternative method is to use hydrogen in enrichment or induction. To investigate the combustion characteristics of this dual fuel engine, a single cylinder diesel research engine was converted to utilize hydrogen as fuel. Hydrogen was introduced to the intake manifold using a mixer before entering the combustion chamber. The engine was run at a constant speed of 2000 rpm and variable equivalence ratio. Rate of heat release, rate of pressure rise and cylinder pressure were measured. Introducing hydrogen to the combustion chamber reduced the diesel fuel consumption.